SODIUM ADEQUACY, FIBER, AND NUTRITIONAL STATUS IN RELATION TO BLOOD PRESSURE OF STUDENTS AT SMPN 13 BANDUNG - Divania Putri Salsabila Gosal; Delita Septia Rosdiana; Fajria Saliha Puspita Prameswari; Asti Dewi Rahayu Fitrianingsih (HEARTY, 2026)
Hypertension is a growing health concern that can begin in adolescence and persist into adulthood. Nutritional factors such as nutritional status, sodium intake, and fiber intake play a key role in influencing blood pressure. This study aims to examine the relationship between nutritional status, sodium adequacy, and fiber adequacy with the incidence of hypertension among junior high school students. This research employed a cross-sectional design with a total of 64 students selected through purposive sampling. Nutritional status was assessed using Body Mass Index-for-Age (BMI/A), while sodium and fiber adequacy were measured using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Blood pressure was measured using a digital sphygmomanometer. Data were analyzed using the Spearman correlation test. The findings showed a significant relationship between nutritional status, sodium adequacy, and fiber adequacy with both systolic and diastolic blood pressure (p < 0.05). Nutritional status had a positive correlation with blood pressure, while sodium intake and fiber intake showed a negative correlation. There is a significant association between nutritional status, sodium adequacy, and fiber adequacy with blood pressure in adolescents. Promoting balanced nutrition from an early age is important to prevent the onset of hypertension.